COMPARATIVE STUDY OF STOCK PRICE INDEX ON EUROPEAN STOCK EXCHANGES BEFORE AND AFTER BREXIT UK STOCK PRICE IN EUROPE - Endah Tri Wahyuningtyas; Dina Anggraeni Susesti; Muis Murtadho (UNUSA Press, 2021)
This study was conducted to analyze the comparison of the impact of Britain to Exit (Brexit) on the UK Stock Price Index in the European region. The sampling countries in this study include four European countries, namely Denmark, France, Germany, and England. This research method uses quantitative research by comparing stock price index data before and after the UK's exit from the European Union. This research is an event study research that is analyzing the market reaction due to an event or the publication of an announcement. Results from this study were that the CSE index Denmark, France CAC index, the index HDAX Germany has a significant influence before and after Brexit Britain while Britain's FTSE index had no impact on the stock price index volatility before and after Brexit. This shows that the investment decisions of investors in Denmark, France, and Germany were greatly influenced by the Brexit announcement so that the stock price indexes in these three countries experienced significant movements. While the Brexit announcement does not affect the decisions of investors in the UK itself because this Brexit event does not contain strong information so that market participants do not react before and after the event.